Emancypowanie się słów. Nauczanie słownictwa a procesy leksykalizacyjne - Pastuch, Magdalena (Postscriptum Polonistyczne, 2020)
This article discusses the possibility of using the concept of lexicalization in teaching Polish as a foreign language. The author presents different views of lexicalization in the works of linguists and she advocates that there is a need for a broad understanding of this phenomenon. The suggested strategy refers to glottodidactic practice. The discussed examples prove that processes that are common (such as breaking ethymological and formative ties) lead to the emancipation of a lexical item, which is no longer regarded as belonging to a certain semantic field. A similar situation occurs when graphic conventions interfere – they can disguise the semantic or formal origin of a lexem. The aim of the strategies suggested in the article is to restore the awareness of the very existence of some ties between words. According to the author it makes the process of building vocabulary easier for foreigners.